From N-vinylpyrrolidone anions to modified paraffin-like oligomers via double alkylation with 1,8-dibromooctane: access to covalent networks and oligomeric amines for dye attachment - Obels, Daniela; Lievenbrück, Melanie; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2016)
The double alkylation of N-vinylpyrrolidone (N-VP) with 1,8-dibromooctane yields paraffin-like oligomeric chains bearing polymerizable vinyl moieties. These oligomers were radically crosslinked in bulk with N-VP as co-monomer yielding swellable polymer disks. The vinylic side groups of the N-VP oligomers allow thiol–ene click reactions with 2-aminoethanethiol hydrochloride to obtain reactive amino-functionalized oligomers. Further modification of the free amino groups with 1,4-difluoro-9,10-anthraquinone (DFA) yields red-colored oligomeric anthraquinone dyes. The final reaction of DFA-substituted N-VP oligomers with Jeffamine® M 600 leads to blue-colored and branched oligomers with poly(ethylene glycol) side chains.
Keywords: double alkylation; modified N-vinylpyrrolidone; oligomeric anthraquinone dye; paraffin-like oligomer; radical thiol-ene click reaction